Financial Inclusion and Macroeconomic Performance in Nigeria - A., Lawal N.; A., Sulaiman L.; O., Migiro S. (Journal of Economics and Behavioral Studies, 2018)
The paper examines the relationship between financial inclusion and macroeconomic performance in Nigeria from 1981 to 2014. The data for the study were sourced from Central Bank of Nigeria statistical bulletins. The study employs the Ordinary Least Square and Granger Causality tests as estimation techniques. From the result, using the coefficient, Gross Domestic Product (GDP) is positive at constant of 2573.946. This means that when all variables are held constant, there will be a positive variation up to 2573.946 units in GDP. This implies that there is a significant and positive effect of financial inclusion on macroeconomic performance in Nigeria. It is concluded that Credit to the Private Sector as a ratio of GDP (CPS/GDP), Money Supply as a ratio of GDP (MS/GDP), and Numbers of Bank Branches (NBB) have a unidirectional relationship to GDP – while Currency Out Banks (COB), Interest Rate (INT) and Total Saving (TSA)are independent of GDP. The study therefore recommends that the government and the Central Bank of Nigeria should improve on the facilitation of credit to the private sector, and money supply should be properly managed. The Central Bank of Nigeria should encourage the provisions of more bank branches to rural and urban areas in order to promote easy access to financial services.